ANALISIS TINGKAT KEPUASAN MAHASISWA TERHADAP LAYANAN PENDIDIKAN PADA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MATARAM - Junaidi Sagir; Alamsyah Abubakar; Emilia Septiani (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
The purpose of this study is to measure satisfaction compared to performance on educational services for students of the Faculty of Economics and Business, University of Mataram, using the servqual model from Parasuraman et.al. which consists of fives dimensions, namely Tangible, Realibility, Responsiveness, Assurance and Emphaty. Respondents consisted of 135 students who were selected by purposive sampling from 3 majors which were evenly divided 45 students for each department. Data were analyzed using the Customer Satisfaction Index (CSI) and the Importance Performance Analysis (IPA).From the analysis it was found that: the average level of satisfaction in education services got a score of 15.5 with the IKM = 72.48% which was at the level of